A method for investigating the influence of rainwater on the useful life of idlers in pipe belt conveyors during seasonal operations. (November 2022) - dos Santos e Santos, Leonardo; Kleyson da Silva Soares, Werner; Roberto Campos Flexa Ribeiro Filho, Paulo
Highlights: Accelerated weathering of idlers using rainwater and chemical oxidizing. Effect of the seasonal shutdown on idlers' useful life. Case study of seizing idlers in a coal handling system. Abstract: Pipe conveyors are specially designed equipment for bulk solids handling in rough terrain regions or environmental-sensitive processes. Their structures are typically exposed to the weather, which allows dust and rainwater to access the idlers sealing along the conveyor, favored by the geometry of the panels. The steel idlers are manufactured by machining, welding, and assembling processes and tightness-test standards are performed to assess the sealing effectiveness. However, current methods do not address specific pipe conveyor characteristics or predominantly stationary conditions, such as seasonal shutdowns and long spare-part storage time. This study proposes an accelerated weathering method for investigating the influence of rainwater on the useful life of steel idlers applied to seasonal operations of pipe conveyors. A measurement apparatus was developed and a case study was conducted in a coal-handling system, using chemical oxidizing and rainwater. The results indicated the bearings' moisture-corrosion caused by water ingression and seal compression, due to the absence of seals and axial freedom of the bearings, respectively. The proposed method presented a desirable evaluation strategy using a non-parametric test for small-sampled trials, which covered the sealing design review, storage condition inspection, and test self-assessment. Main preventive actions include sealing redesign and changing idlers' storage procedures.